"Wochenblatt.pl" and "Der Nordschleswiger" - magazines of the German minority in search of their own way = "Wochenblatt.pl" i "Der Nordschleswiger" - pisma mniejszości niemieckiej w poszukiwaniu własnej drogi. - Jas-Koziarkiewicz, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
National and ethnic minorities strive to preserve and develop their distinct identities. It is done, among other things, through the actions of organizations representing interests of the minorities and through the activity of the media which address and are created for the minorities.
Keywords: press; German minority; Poland; Denmark; "Wochenblatt.pl"; "Der Nordschleswiger"; prasa; mniejszość niemiecka - Polska; Dania